ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI PADI DI KECAMATAN SUOH KABUPATEN LAMPUNG BARAT - Barnawan, Barnawan; Sari, Yuni Elmita (Universitas Muara Bungo, 2025)
West Lampung Regency has 31,120 hectares of land used for lowland rice cultivation, according to 2023 data from the local Agriculture Office. Over the past three years, rice productivity in this region has been unstable. However, in 2024, the figure dropped significantly to 47.03 tons per hectare (BPS Lampung Province). This study was conducted in Suoh District, West Lampung Regency, from January to February 2025. The research focuses on income calculation, business feasibility, and analysis of the R/C ratio (Return and Cost Ratio). The research location was limited to Pekon Tuguratu, with a sample of 84 farmers. Data collection methods included field surveys and in-depth interviews, whiledata analysis used quantitative descriptive methods. The findings show that the average income from rice farming in Suoh District was Rp 2,182,001.06, with an average total production cost of Rp 8,865,300.52 and an average land area of 1.44 hectares. The R/C ratio was 1.37, meaning that for every Rp 1 spent on production costs, farmers earned Rp 1.37, indicating efficient and feasible rice farming operations. Meanwhile, the B/C ratio was 1.25, confirming that the farming business was profitable.